Correction to: Modelling [18F]LW223 PET data using simplified imaging protocols for quantification of TSPO expression in the rat heart and brain. - MacAskill, Mark G.; Wimberley, Catriona; Morgan, Timaeus E. F.; Alcaide‑Corral, Carlos J.; Newby, David E.; Lucatelli, Christophe; Sutherland, Andrew; Pimlott, Sally L.; Tavares, Adriana A. S. (European Journal of Nuclear Medicine & Molecular Imaging, 2024)
This document is a correction notice for an article titled "Modelling [18F]LW223 PET data using simplified imaging protocols for quantification of TSPO expression in the rat heart and brain" published in the European Journal of Nuclear Medicine & Molecular Imaging. The correction notice addresses errors in the original article and provides the accurate information. The corrections include changes to numerical values and clarifications in the text. Additionally, some figures in the original article were incorrect and have been corrected in the notice. The publisher, Springer Nature, remains neutral and unbiased in relation to jurisdictional claims and institutional affiliations.